1982
DOI: 10.1093/ageing/11.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Bacteriuria in Old Age

Abstract: Among 352 residents of a home for the elderly, who were fully mobile and devoid of most predisposing factors for bacteriuria, 19% of men and 27% of women had two positive cultures within two months. Positive conversion at one year among men and women negative at entry was 11% and 23% respectively, negative conversion of bacteriurics 22% and 27%. Subjects bacteriuric at entry but sterile at six months had a 77% (men) and 44% (women) reinfection rate at 12 months. The data indicate firstly that a significant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Significant bacteriuria as used in the present study is the most com mon criterion in clinical practice [3,6,7], Determination of the urinary leukocytes has been recommended as a screening method for significant bacteriuria [6]. It ap pears from the present series that bacterial staining is the best screening method for as sessing significant bacteriuria (table V).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Significant bacteriuria as used in the present study is the most com mon criterion in clinical practice [3,6,7], Determination of the urinary leukocytes has been recommended as a screening method for significant bacteriuria [6]. It ap pears from the present series that bacterial staining is the best screening method for as sessing significant bacteriuria (table V).…”
Section: Discussionmentioning
confidence: 70%
“…The prevalence of urinary tract infection (UTI) is known to increase with age [3,7,10]. There is no data on urinary 'abnormalities' and its significance in the very old.…”
Section: Introductionmentioning
confidence: 99%
“…Among elderly people living in institutions of various kinds, the prevalence of ABU is even higher, varying between 19% and 33% in men and between 18% and 50% in women (7 -10). Studies have also shown that bacteriuria among the elderly can vary over time (7,8,11).…”
mentioning
confidence: 99%
“…Physiological changes during pregnancy, including dilatation of the ureters and renal pelvis, allow bacteria in the bladder to reach the kidneys and produce pyelonephritis (Shortliffe, 1986). 20% to 30% of bacteriuric pregnant women develop an acute pyelonephritis during www.intechopen.com pregnancy if untreated, in contrast to only 1-3% of pregnant women who received antibiotics (Golan et al, 1989, Kasviki-Charvati et al, 1982. It is well documented that acute pyelonephritis in late pregnancy is associated with prematurity (Gilstrap et al, 1981, McGrady et al, 1985, Mittendorf et al, 1992.…”
Section: Pregnant Womenmentioning
confidence: 99%